Crop cafeteria – An effective tool to showcase diversity and choice of cultivars to farmers - Mahla, H R; Rathore, V S; Bhatt, R K; Yadav, O P (Indian Farming, 2020)
Crop yield in given agro-climatic conditions are determined by interactive effects of many factors. Amongst these, choice of suitable variety and appropriate agro-techniques are major determinants of crop yields. Majority of farmers, particularly in hot arid regions have been using old/traditional varieties and hardly following recommended seed rate and spacing due to lack of knowledge. Popularization of improved crop varieties along with better agro-techniques among the farming community through different extension and training programme has been advocated but it takes lot of time for adoption on large scale. Therefore, for disseminating the significance of improved varieties and crop management practices among the farming community a concept of Crop Cafeteria was executed where diverse improved varieties along with suitable crop management practices for pearl millet, moth bean, mung bean and cluster bean were demonstrated at Research Farm of ICAR- CAZRI. Thousands of farmers visited the Crop Cafeteria and witnessed that yield can be increased 2-3 times by adopting improved crop varieties and crop management practices compared to their conventional management with traditional varieties.